Warfarin involvement, in comparison to NOACs, in the development of systemic atherosclerosis - Mihaila, Romeo Gabriel (Biomedical papers, 2022)
Adverse effects of drugs are one of the objective criteria used for choosing the most appropriate anticoagulant. It is worrying that warfarin may be involved in the progression of systemic atherosclerosis, as more and more articles suggest. Warfarin has been widely used in the past and has greater efficacy compared to dabigatran in patients with mechanical heart valves; there is an antidote to it and it is cheap. Unfortunately, warfarin inhibits the synthesis and activity of Matrix-Gla-Protein, which is the major vitamin K-dependent inhibitor of arterial calcification - an active process associated with atherosclerosis, stimulated by inflammatory mechanisms. Vitamin K antagonizes the NF-κB signaling mechanism and contributes to the prevention of arterial calcifications. Warfarin given in experimental animal models of atherosclerosis contributed to the occurrence of an increased number of aortic calcifications. Warfarin treatment used in clinical trials was associated with the progressive increase of coronary atheroma calcification. Younger patients are more sensitive to warfarin-related arterial calcifications compared to older patients, due to warfarin-induced cellular senescence changes. Non-vitamin K antagonist direct oral anticoagulants do not interact with vitamin K. Edoxaban reduces the inflammatory process in the vascular walls and the proliferation of smooth vascular muscle cells, so it is involved in the prevention of vascular maladaptive remodeling process. Apixaban is able to stabilize the coronary atherosclerotic process. Randomized clinical trials are needed to evaluate the impact of warfarin on plaque stability and cardiovascular evolution of patients.
Keywords: atherosclerosis; direct oral anticoagulants; thrombosis; vascular calcification; warfarin